Effective Leadership and its Impact on an Organisation’s Success - Schuetz, Agnieszka (Journal of Corporate Responsibility and Leadership, 2017)
The aim of this literature review paper is to show the most important differences between a manager and a leader and to present various definitions of leadership in the context of an organisation’s market success. The author intends to highlight the most popular approaches to leadership, together with the concept of positive leadership, present selected factors influencing leadership effectiveness, including principles of a personal contract, and give ‘food for thought’ for present and future leaders willing to succeed in more and more demanding environment. Finally, a case study of Henri Strzelecki, a charismatic British leader and manager of Polish extraction is described. The findings of the case study are based on the author’s observations and interviews constituting the ethnographic research carried out both in the Polish and the English premises of Mr. Strzelecki’s company.